Rehabilitation of sinkholes and subsidences on Dolomitic Land Ekurhuleni Metropolitan Municipal Area of Jurisdiction Gauteng South Africa - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.